Synergy of Administrative and Criminal Law Enforcement as an Effort to Prevent and Eradicate Corruption in Procurement of Goods and Services in Government Environment - Maksum, Umar; Suparno, Suparno (Journal Of Social Science (JoSS), 2025)
Corruption in government procurement of goods and services remains a critical issue in Indonesia, undermining national development and public trust. This research examines the synergy between administrative and criminal law enforcement as a strategy to prevent and eradicate corruption in this sector. The study highlights the vulnerabilities in procurement processes, such as regulatory gaps, weak oversight, and the misuse of discretionary authority, which often lead to corrupt practices like bid rigging and fictitious procurement. The objective is to analyze the effectiveness of integrating administrative and criminal law mechanisms to create a more transparent and accountable procurement system. Using a normative juridical method, the research reviews legal frameworks, including Law No. 31 of 1999, Law No. 20 of 2001, and Presidential Regulation No. 16 of 2018, alongside secondary legal materials. The findings reveal that while Indonesia has a comprehensive legal foundation, inconsistencies in enforcement and overlapping institutional authorities hinder effectiveness. The study emphasizes the need for clear distinctions between administrative violations and criminal acts, as well as improved coordination among supervisory bodies like APIP, LKPP, and the KPK. The research concludes that a synergistic approach, combining administrative oversight as a preventive measure and criminal law as a last resort, is essential. Recommendations include harmonizing regulations, establishing joint SOPs, and enhancing training for procurement officials. These measures aim to reduce legal uncertainty and foster a corruption-free procurement environment.